Evaluation of biological parameters of Eriopis connexa (Germar, 1824) and Coleomegilla maculata (DeGeer, 1775) (Coleoptera: Coccinellidae) fed with alternative prey developed at the Integrated Center for Pest Management - UFRRJ - D. P. Almeida (Scientific Electronic Archives, 2020)
The aim of this work was to evaluate the potential of live larvae of Drosophila melanogaster (Meigen) (Diptera: Drosophilidae) as alternative prey used in the E. connexa and C. maculata rearings developed at the Integrated Center for Pest Management (CIMP) (UFRRJ, Seropédica campus, state of Rio de Janeiro, Brazil), in comparison to the use of flour moth eggs, Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae), sterilized by ultraviolet radiation. The obtained results showed that the larvae of the two lady beetles developed adequately, as well as generating fertile adults and viable eggs when fed on live larvae of D. melanogaster, similar to E. kuehniella eggs. It can be concluded that the live larvae of this fly can replace the eggs of the flour moth in the rearing of the two lady beetles in the laboratory.